2016
DOI: 10.4103/0366-6999.192784
|View full text |Cite|
|
Sign up to set email alerts
|

Porcine Small Intestinal Submucosa Mesh for Treatment of Pelvic Organ Prolapsed

Abstract: Background:Pelvic organ prolapse (POP) is a major health concern that affects women. Surgeons have increasingly used prosthetic meshes to correct POP. However, the most common used is synthetic mesh, and absorbable mesh is less reported. This research aimed to evaluate the clinical effectiveness of porcine small intestinal submucosa (SIS).Methods:Consecutive forty POP patients who met the inclusion criteria underwent pelvic reconstruction surgery with SIS between March 2012 and December 2013. The patients’ cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A 1-year study of sling with SIS reported that although no erosion but anterior repair had a higher recurrence rate of 40%. [46]…”
Section: Stress Urinary Incontinence Surgerymentioning
confidence: 99%
“…A 1-year study of sling with SIS reported that although no erosion but anterior repair had a higher recurrence rate of 40%. [46]…”
Section: Stress Urinary Incontinence Surgerymentioning
confidence: 99%
“…Acellular tissue matrices (e.g., small intestinal submucosa (SIS) [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], bladder acellular matrix (BAM) [ 33 , 34 ], amniotic membrane (AM) [ 35 ], and dermis [ 36 ]) preserve the morphology of native tissues. With the aim to preserve the advantages of both natural and synthetic materials and to overcome their limitations, hybrid scaffolds generated by a combination of both types of materials have been recently tested [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reconstruction of pelvic floor with mesh is the main surgical method for POP [ 5 ]. Compared with synthetic material mesh, biomaterial mesh has the advantages of good biomechanical compliance and excellent biocompatibility [ 6 ].…”
Section: Introductionmentioning
confidence: 99%